SUPPORT FAMILY RELATIONSHIP WITH QUALITY LIFE OF A DIABETIC MELLITUS PATIENT AT ESHMUN HOSPITAL - Melya Rima, Oka; Debora, Rezky; Elysabeth Tambunan, Chintia; Risna Hutagalung, Siti; Nurhayati, Evalatifah; Lubis, Lisnawati (Jurnal Kesehatan Kusuma Husada, 2025)
This study examines how family support and the quality of life of patients with diabetes at Eshmun Hospital are related. Diabetes melitus is chronic disase that reqires longtem management, where family support has an important role in imprving the patint's quality of life. This study uses a quanttative method with a crosectional research design. The research sample is a diabetic mellitus patient who visited Eshmun Hospital, with a purposive sampling techniq. Data were collected using a structured questionaire that included aspects of family support and the patient's quality of life, then analyz using a chi-square statistical test. The results showed a signficant relationship betwen family support and quality of life in patients with diabetes melitus (p-value < 0.05). in Eshmun Hospital. Good family support, such as emotional, instrumental, evaluative, and informational support, has ben shown to have a positive effect on the patient's quality of life. With the support of family, patients feel more motivated to undergo treatment and maintain a healthy lifestyle. This is study recommends the importance of the role of the family in supporting diabetic mellitus patients to improve their quality of life